CONCEPTUAL MODEL OF OPTIMIZATION STUDY OF SMALL OIL FIELD DEVELOPMENT WITH HIGH WATER CUT BY PRODUCTION ENGINEERING, RESERVOIR ENGINEERING, AND RESERVOIR SIMULATION ANALYSIS - MARTA (NIM : 22208040), DONAL
X Field is an oil and gas field that has OOIP about 16 MMSTB. Beside its potential, this field has high water cut (about 85%-92%). Because of that, optimization study is necessary must be done to predict oil recovery potential. The methodologies of study consist of production engineering, reservoir engineering, simulation engineering, and economic analysis. According to production engineering analysis, the optimum liquid rate is 444.4 stb/day where the Production Index of reservoir is 0.52 stb/day-psi and Injection index of reservoir is 0.49 stb/day- psi. According to reservoir engineering analysis, Field X needs 6 production wells and 6 injection wells in order to produce oil in optimal rate with average oil rate is about 280.7 stb/day with injection rate is about 2589 stb/day. The optimum water rate in each well is 400 stb/day where the recovery factor is about 2.33%. Scenario with Natural Depletion shown optimal result with recovery factor about 5.7% if it developed with 6 production wells with distribution pattern 1 where perforation are in 1-5-6 layers. Scenario with Waterflooding shown that optimal result with recovery factor is about 15.19% if it developed with 6 production wells and 6 injection wells with two spot patterns where production wells are perforated in layer 1 and injection are started at 1 July 2014. According to economic analysis, scenario with Natural Depletion (US$ 594,558.14) is more economic compared to scenario with Waterflooding (-US$ 2,067,131.39).